Design elements regarding to cultural factors of Iranian carpet - Abdul Rahman, Ahmad Rizal; Abedini, Ahmad (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
The aspect of physical and nonphysical factors influence to the success of new product to be competence in the current market. Culture factors is one of the elements which need to be considered by designer during new product development process. This paper examine references of cultural factors to accommodate with appropriate design elements preferences on Iranian carpet which were created based on people’s beliefs, tradition and product function. This study involved with qualitative method where interview has been conducted to identify prior culture factors influence to product to match with relevant design element which have strong influence to the product. This study can be useful to the designers in designing cultural product for the future. This work aimed to assist designers in designing product based on culture for specific users, which can also be beneficial for others interested in developing products based on culture factors.